Effectiveness of nurse-led care in patients with rheumatoid arthritis: a systematic review and meta-analysis - Dan Liu; Li Liu; Lin Yang; Ting Wen; Peng Xiang; Guifang Pi (BMJ Open Quality)
Objectives This study sought to assess the effectiveness of nurse-led care (NLC) in patients with rheumatoid arthritis (RA).Methods We conducted a comprehensive search of the Cochrane Library, Web of Science, PubMed, Embase, CINAHL, ClinicalTrials.gov databases and the references from relevant literature published prior to May 2023. Two independent reviewers assessed the studies using population/intervention/comparison/outcome/study criteria, and quantitative tools were used to gauge the methodological quality of the included studies. Independent quality assessments were carried out using the Cochrane Collaboration’s risk-of-bias tool. Effect sizes were determined using mean difference (MD) or standardised mean difference (SMD) with corresponding 95% CIs.Results Ultimately, 14 articles were included, encompassing a total of 3369 RA patients. NLC exhibited significant advantages in the primary outcome, disease activity (MD =−0.09, 95% CI (−0.17 to –0.01)), and the secondary outcome, self-efficacy (MD=0.40, 95% CI (0.03, 0.77)). In subgroup analysis, NLC was more effective in reducing disease activity compared with usual care (MD=−0.15, 95% CI (−0.26 to –0.04)), and there was no significant difference in disease activity reduction between NLC and rheumatologist-led care (MD=−0.02, 95% CI (−0.14, 0.10)). In terms of self-efficacy, no significant difference was observed between NLC and usual care (SMD=0.56, 95% CI (−0.09, 1.21)) or between NLC and rheumatologist-led care (SMD=0.20, 95% CI (−0.19, 0.59). When comparing other secondary outcomes (pain, satisfaction, quality of life, fatigue, stiffness, physical function and psychological status), the effectiveness of NLC for RA patients was similar to that of the control group, with no statistically significant differences.Conclusions NLC proves highly effective in managing RA patients, surpassing usual care and equating to rheumatologist-led care in primary and some secondary outcomes. It may be feasible to allow nurses to participate in the disease management of some RA patients instead of doctors.PROSPERO registration number CRD42022362071.